Private Participation in Transport : Lessons from Recent Experience in Europe and Central Asia - Monsalve, Carolina (World Bank, Washington, DC, 2012)
Facing fiscal constraints, many governments in Central and Eastern Europe and Southeastern Europe have pursued private finance for transport infrastructure more to move investments off budget than to improve efficiency and services. Results have been mixed and suggest a need to focus more on public-private partnerships (PPPs) that can achieve value for money. Today's economic environment will reduce the potential for PPP projects in the short term. Some PPP projects at an advanced stage of procurement may need additional public support, while ambitious projects may need to be phased to reduce their scale to what the market can absorb.